Paraphrasing Method Based on Contextual Synonym Substitution - Ari Moesriami Barmawi; Ali Muhammad (LPPM ITB, 2019)
Generating paraphrases is an important component of natural language processing and generation. There are several applications that use paraphrasing, for example linguistic steganography, recommender systems, machine translation, etc. One method for paraphrasing sentences is by using synonym substitution, such as the NGM-based paraphrasing method proposed by Gadag et al. The weakness of this method is that ambiguous meanings frequently occur because the paraphrasing process is based solely on n-gram. This negatively affects the naturalness of the paraphrased sentences. For overcoming this problem, a contextual synonym substitution method is proposed, which aims to increase the naturalness of the paraphrased sentences. Using the proposed method, the paraphrasing process is not only based on n-gram but also on the context of the sentence such that the naturalness is increased. Based on the experimental result, the sentences generated using the proposed method had higher naturalness than the sentences generated using the original method.